Electronic ionisation-induced annealing of pre-existing defects in Al2O3 and CaF2 single crystals. Issue 4 (16th February 2022) - Izerrouken, M.; Hazem, R.; Kuzeci, S.; Tav, C.; Yahsi, U.; Limam, S.
ABSTRACT: Electronic ionisation-induced annealing of pre-existing defects in CaF2 and Al2 O3 single crystals has been investigated. Pre-existing defects (vacancies and interstitials) and defect aggregates were first induced in both crystals by fast neutrons irradiation and then irradiated by 90 MeV Xe ions. After irradiation, the samples were characterized using Doppler Broadened Emission Spectroscopy (DBS). The S parameter and average S values obtained for the neutrons irradiated samples are compared with results obtained for samples irradiated by neutrons + Xe ions. Results of these experiments revealed ionisation-induced pre-existing defect annealing in Al2 O3 while generating more defects in CaF2 . It is also found that the defect recovery rate in Al2 O3 crystal depends on the Xe ions fluence that confirms the different mechanisms of defect formation in both materials. The electronic ionisation and excitation energy are transferred to the defects formation in the self-trapped exciton (STE) mechanism resulting in defect formation in CaF2 . Whereas in the case of Al2 O3, it is transferred to electron–phonon coupling leading to lattice heating, which causes the annealing of the pre-existing defects.